Investigating the Influence of Perceived Quality, Perceived Value, and Customer Satisfaction on Loyalty Towards Huawei Mate50 Smartphones - Jintao Guo; Nuttawut Rojniruttikul (My University, 2024)
This study investigates the influence of perceived quality, perceived value, and customer satisfaction on customer loyalty towards Huawei Mate50 smartphones in Thailand.The authors collected data from 400 smartphone users using a structured questionnaire and analyzed the data using structural equation modeling (SEM).The findings reveal significant positive relationships between perceived quality, perceived value, customer satisfaction, and loyalty.However, the study has limitations, such as the use of convenience sampling and the focus on a single smartphone model.The authors suggest that future research should explore the impact of moderating variables and employ longitudinal designs to better understand the dynamics of customer loyalty in the smartphone industry.The study contributes to the understanding of consumer behavior in the smartphone market and provides practical implications for manufacturers seeking to enhance customer loyalty.
Keywords: Customer Satisfaction; Value (mathematics); Perceived quality; Customer value; Technology Adoption and User Behaviour